Feminizing Genioplasty: A Review of Operative Techniques and Clinical Outcomes. Issue 2 (June 2023) - Khetpal, Sumun; Baker, Nusaiba F.; Hu, Vivian; Dejam, Dillon; Patel, Harsh; Morgan, Katarina B. J.; Wolfe, Erin M.; Lee, Justine C.
Background: Facial feminization procedures can be performed to alleviate gender dysphoria among transfeminine or non-binary patients. Moreover, the chin may play an important role in immediate identification and recognition of the face as cis-masculine or cisfeminine, and thus, can be addressed via feminizing genioplasty in the transfeminine population. The purpose of this study was multi-fold: 1) perform a systematic literature review to investigate the current methods utilized to feminize the chin, and 2) study clinical outcomes within an institutional cohort undergoing feminizing genioplasty. Methods: A systematic literature review was conducted in order to survey articles that discussed techniques and clinical considerations when performing genioplasty among transgender females and nonbinary patients. In addition, a retrospective review of such patients undergoing genioplasty by the senior author was conducted. Variables collected included demographic factors, operative details, and postoperative outcomes. Results: Query of the PubMed database resulted in forty articles after removal of duplicates. Eleven studies that discussed surgical technique about genioplasty in facial feminization surgery were selected for analysis and discussion. Commonly discussed techniques were surgical incision, horizontal and vertical reduction, and material used for fixation. Eighty-seven patients were included in our institutional cohort. Approximately half of the patients underwent 2-piece reduction genioplasty, while 8 patients had 1-piece reduction. Horizontal osteotomies and vertical osteotomies were performed in the majority of patients. About one-third of patients received osseous augmentation via centralized osteotomy segments and cranial bone grafts. Conclusions: The core tenets of feminization of the chin lie in the reduction in both horizontal and vertical planes, as well as the creation of harmony with other facial structures. Our analysis presents an updated review of these principles, as well as an in-depth analysis of the senior author's technique in feminization of the chin in transgender women.